Modeling and system analysis of floating underwater vehicle with variable mass and center of gravity. (1st January 2023) - Li, Xinyang; Wen, Hao; Fu, Jian; Zhang, Xu; Zhou, Hexiong; Yao, Baoheng; Lian, Lian; Yu, Dequan; Mao, Lifeng
Abstract: This research proposes a new dynamic model for underwater vehicles with variable mass and center of gravity. The variation of center of gravity and moment inertia of the vehicle is related to the convolution of mass changing rate function and trajectory function. Furthermore, the center of gravity varies obviously if exists disturbance and variable mass parcels. In comparison of fixed center of gravity model, the variation of center of gravity impacts the maneuverability of underwater vehicles greatly. As extended applications, this research provides theoretical basis for the design of floating mining craft, underwater dredging craft and other variable mass underwater vehicles. Highlights: The dynamic models of the Variable Mass Underwater vehicle (VMUV) are proposed. The relationships among the time-varying parameters are established. The motion simulation of the models is proposed.